Soybean Production in the 1976-2002 Period: Performance and Impact on the Agrarian Structure of the Province of Córdoba (Argentina) - Civitaresi, Hector Martín; Universidad Nacional de Río Negro,Argentina. (Editorial Pontificia Universidad Javeriana, 2012)
The growth of the oilseed complex in Argentina began in the mid-1970s and was consolidated in the two following decades according to the dynamics of foreign demand, the existing agro-ecological advantages for the production of oilseeds, and the incorporation of technological advances and sectorial and macroeconomic policies implemented by successive governments. In the province of Cordoba, the development of the complex is based on the production of soybeans and soybean industrial products (oil and pellets). While Argentinian soybean production has reached levels of international competitiveness, there is a process of concentration of land ownership and use and of the industry itself, among other socioeconomic impacts. There has also been a process of agriculturization based on soybean, displacing other agricultural activities, and environmental issues such as the contamination of resources through the intensive use of agrochemicals.